2018
DOI: 10.1016/j.puhe.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A small-scale study investigating staff and student perceptions of the barriers to a preventative approach for adolescent self-harm in secondary schools in Wales—a grounded theory model of stigma

Abstract: The findings of this study offer an explanation on the exclusion of adolescent self-harm from preventative work in secondary schools. The stigma model demonstrates that adolescent self-harm is excluded from the socio-cultural norms of the institutional setting. Applying the UK Equality Act (2010), this is discrimination. Further research on the institutional-level factors impacting adolescent self-harm in the secondary school context in England and Wales is now urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
10
0
5
Order By: Relevance
“…Concealability NSSI scars tend to be recognizable as self-inflicted (Ho, Jones, & Anderson, 2018) Feelings of shame (Lesniak, 2010;Rosenrot & Lewis, 2018) Hiding/covering/removing scars 2014; Hodgson, 2004;Lesniak, 2010) Being instructed to hide/cover scars or being forced to prove NSSI (Parker, 2018) Marker for mental illness (Burke, Olino, & Alloy, 2017) Falsifying narratives (Hodgson, 2004;Lesniak, 2010) Avoiding activities (e.g., swimming; (Newton & Bale, 2012;Parker, 2018) Ongoing urges, notions of recovery (Lewis, Kenny, Whitfield, & Gomez, 2019;Wadman et al, 2017) Visible scars as triggering (Burke et al, 2017) Fear of impact to career prospects (Long, 2018) Scars do not necessarily indicate current self-injury (Chandler, 2014) "Just stop it" Judgment from others leading to continued self-injury (Long, Manktelow, & Tracey, 2015) Belief that NSSI can easily be stopped (Wadman et al, 2017) Frustration with continued self-injury (Sandy & Shaw, 2012) Being told how expensive dressings are (Newton & Bale, 2012) What the public thinks about the peril of NSSI How an individual perceives the peril of their own NSSI What an individual expects others to think about the peril of their NSSI How people are treated as a result of beliefs about the peril of NSSI Peril Conflation of NSSI and suicide…”
Section: How Concealability Influences An Individual's Expectations O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Concealability NSSI scars tend to be recognizable as self-inflicted (Ho, Jones, & Anderson, 2018) Feelings of shame (Lesniak, 2010;Rosenrot & Lewis, 2018) Hiding/covering/removing scars 2014; Hodgson, 2004;Lesniak, 2010) Being instructed to hide/cover scars or being forced to prove NSSI (Parker, 2018) Marker for mental illness (Burke, Olino, & Alloy, 2017) Falsifying narratives (Hodgson, 2004;Lesniak, 2010) Avoiding activities (e.g., swimming; (Newton & Bale, 2012;Parker, 2018) Ongoing urges, notions of recovery (Lewis, Kenny, Whitfield, & Gomez, 2019;Wadman et al, 2017) Visible scars as triggering (Burke et al, 2017) Fear of impact to career prospects (Long, 2018) Scars do not necessarily indicate current self-injury (Chandler, 2014) "Just stop it" Judgment from others leading to continued self-injury (Long, Manktelow, & Tracey, 2015) Belief that NSSI can easily be stopped (Wadman et al, 2017) Frustration with continued self-injury (Sandy & Shaw, 2012) Being told how expensive dressings are (Newton & Bale, 2012) What the public thinks about the peril of NSSI How an individual perceives the peril of their own NSSI What an individual expects others to think about the peril of their NSSI How people are treated as a result of beliefs about the peril of NSSI Peril Conflation of NSSI and suicide…”
Section: How Concealability Influences An Individual's Expectations O...mentioning
confidence: 99%
“…Common misconceptions include that it is an attention-seeking or manipulative behavior (Lewis, Mahdy, Michal, & Arbuthnott, 2014; Lloyd, Blazely, & Phillips, 2018; Sandy, 2013; Scourfield, Roen, & McDermott, 2011), that it is circumscribed to teenagers (Hughes et al, 2017; Oldershaw, Richards, Simic, & Schmidt, 2008) or girls (Lewis et al, 2014), and that it is suicidal (Kumar, Pepe, & Steer, 2004) or superficial and transitory (Mitten, Preyde, Lewis, Vanderkooy, & Heintzman, 2016; Oldershaw et al, 2008). These misconceptions generate stereotypes about NSSI that may result in prejudice and discrimination in the form of negative judgments (Long, 2018), reduced access to services (Anonymous, 2016), or removal of autonomy (Parker, 2018). People who self-injure may internalize NSSI stereotypes, resulting in diminished self-esteem and a reluctance to seek support (Chandler, 2014; Long, 2018), despite the potential benefits of doing so (Hasking, Rees, Martin, & Quigley, 2015).…”
mentioning
confidence: 99%
“…6,27 However, it is important to consider that suicidal behavior is still treated as a taboo, a stigma in the school context, resulting in judgmental stances, both by teachers and by other students when observing behavior changes, which can be explained by ignorance, feeling impotence and fear, given the complexity to manage the situation safely and effectively. 12 During the speech, friendship, family, and professional help were appointed with support networks. It is emphasized that social support promotes mental health and prevents mental problems, while the lack of it contributes to the increased incidence of suicidal behavior.…”
Section: Suicidal Behavior and Prevention By Teachersmentioning
confidence: 99%
“…Thus, considering the complexity of the problem and the existence of a portion of the society under suicidal behavior risk, it is necessary, therefore, that the school may start to deal with this issue as something real, existing and present in the students' daily life, in the seek for breaking the complicity of the silence that leads to the denial or the minimization of the suicidal behavior. 12 Therefore, this study aims to analyze knowledge about suicidal behavior and prevention strategies adopted by elementary school teachers.…”
Section: Introductionmentioning
confidence: 99%
“…This stigma has been associated with increased social isolation, deep shame, and lower likelihood of seeking help (Burke et al, 2019). In one study, stigma of NSSI was related to the exclusion of NSSI from prevention programming in secondary schools (Parker, 2018). The author concluded that this met criteria for discrimination according to the UK Equality Act of 2010, highlighting the need for improved efforts toward prevention.…”
Section: Cultural Perspectives For Managing Suicide and Nssimentioning
confidence: 99%